1990
DOI: 10.1111/j.1365-2990.1990.tb00932.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Semliki Forest virus for the rat central nervous system and primary rat neural cell cultures: possible implications for the pathogenesis of multiple sclerosis

Abstract: The neurovirulent L10 strain of Semliki Forest virus (SFV) causes extensive neuronal damage in the central nervous system (CNS) of infected rats, and is probably the cause of death. The avirulent A7 and M9 strains do not cause extensive neuronal damage, but do induce immune-mediated CNS demyelination. In primary CNS cell cultures derived from rats, L10 multiplies more rapidly in neurons than avirulent strains, but infection with both virulent and avirulent strains causes depletion of oligodendrocytes from mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
(26 reference statements)
1
34
0
Order By: Relevance
“…1 e). This confirms previous results for A7 and the virulent L10 strain of SFV (Atkins, 1983 ;Gates et al, 1985 ;Atkins et al, 1990).…”
supporting
confidence: 82%
See 4 more Smart Citations
“…1 e). This confirms previous results for A7 and the virulent L10 strain of SFV (Atkins, 1983 ;Gates et al, 1985 ;Atkins et al, 1990).…”
supporting
confidence: 82%
“…It has previously been shown that infection of glial cell cultures with SFV results in depletion of the upper oligodendrocyte layer Gates et al, 1985 ;Atkins et al, 1990) and that this layer is selectively stained by anti-SFV antibody . SFV-infected oligodendrocytes can also be demonstrated in the animal (Atkins & Sheahan, 1982 ;Sheahan et al, 1983).…”
mentioning
confidence: 99%
See 3 more Smart Citations